2022
DOI: 10.3390/biom12081152
|View full text |Cite
|
Sign up to set email alerts
|

STIM Proteins and Regulation of SOCE in ER-PM Junctions

Abstract: ER-PM junctions are membrane contact sites formed by the endoplasmic reticulum (ER) and plasma membrane (PM) in close apposition together. The formation and stability of these junctions are dependent on constitutive and dynamic enrichment of proteins, which either contribute to junctional stability or modulate the lipid levels of both ER and plasma membranes. The ER-PM junctions have come under much scrutiny recently as they serve as hubs for assembling the Ca2+ signaling complexes. This review summarizes: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…For example, the STIM1 puncta signal reshapes into annular structures when extended synaptogamines (E‐syt) relocate to the central area of these microdomains. Interestingly, E‐syt1 alone induces these ring‐shaped contacts; in contrast, STIM1 by itself can only generate the classical ER‐PMjs clusters 28 . Moreover, distances between the ER and the PM were different depending on the protein involved.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the STIM1 puncta signal reshapes into annular structures when extended synaptogamines (E‐syt) relocate to the central area of these microdomains. Interestingly, E‐syt1 alone induces these ring‐shaped contacts; in contrast, STIM1 by itself can only generate the classical ER‐PMjs clusters 28 . Moreover, distances between the ER and the PM were different depending on the protein involved.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, E-syt1 alone induces these ring-shaped contacts; in contrast, STIM1 by itself can only generate the classical ER-PMjs clusters. 28 Moreover, distances between the ER and the PM were different depending on the protein involved. This finding suggests that different proteins generate different types of ER-PMjs, morphologically and functionally, as both promote different calcium responses.…”
Section: Discussionmentioning
confidence: 99%
“…The ER is a calcium‐ion storage and unique protein synthesis mechanism that is distributed throughout neurons with the presence of multiple domains associated with different functions. One such domain is called EMC, which is located on the ER membrane 63,64 . The location of ER/EMC within neurons reveals their contribution to synaptic plasticity by regulating various cellular processes from protein synthesis to Ca 2+ signaling.…”
Section: The Functions Of Emcmentioning
confidence: 99%
“…We conclude that ESYT1mediated MERC tethering is required for efficient ER to mitochondria Ca 2+ transfer. ER-PM contact sites are responsible for store-operated Ca 2+ entry (SOCE) (Ahmad, Narayanasamy et al 2022). It has been suggested that ESYT1 ER-PM tethering would be activated by and reinforce SOCE (Giordano, Saheki et al 2013, Maleth, Choi et al 2014, Idevall-Hagren, Lu et al 2015, Kang, Zhou et al 2019.…”
Section: Esyt1 Is Required For Er To Mitochondria Ca 2+ Transfermentioning
confidence: 99%